The Construction of Female Leadership Through Polynesian Cultural Values in Disney's Moana - Aliyya Novianti; Novi Sriwulandari; Risma Kartika Dewi (PT Ilmu Data Indonesia, 2026)
Because more and more movies feature leaders from a variety of cultural backgrounds, leadership has emerged as one of the most popular subjects in literary and cultural studies. By incorporating indigenous Polynesian cultural values into the development of its female protagonist, Disney's Moana (2016) presents a unique example of leadership. This study focuses on how Polynesian cultural values construct female leadership, in contrast to earlier research that looked at cultural representation or female identity separately. The goal of this study is to examine how Polynesian cultural values are portrayed and elucidate how Moana's leadership is influenced by these values throughout the narrative. The Moana movie served as the main source of data for this study, which used a descriptive qualitative method. Through the use of documentation techniques, information about leadership and cultural values was gathered through the observation of conversations, visual images, character interactions, and narrative events. Northouse's leadership theory, Kaʻili's concept of Polynesian cultural values, and Barker's theory of cultural representation were used to analyze the data. The results show that respect for ancestors, traditional navigation, community responsibility, harmony with nature, and group decision-making are examples of Polynesian cultural values. These cultural values have a big impact on how Moana develops her leadership traits, which include bravery, empathy, accountability, teamwork, resilience, and dedication to the good of the community. The movie portrays leadership as a cultural practice based on service, accountability, and social harmony rather than as dominance or authority. As a result, Moana represents an alternative model of female leadership based on indigenous customs in addition to promoting Polynesian culture